The Current State of Emergency Psychological Assistance in the Education System - Ulyanina, O.A.; Gayazova, L.A.; Ermolaeva, A.V.; Faizullina, K.A. (Psihologičeskaâ nauka i obrazovanie, 2022)
Scientific interest in providing emergency psychological assistance in crisis situations is based on a practical request, since a crisis incident poses a threat to life and health. The paper presents an analysis of the provision of emergency psychological assistance in the education system. The sample consisted of 3 groups of respondents (12048 individuals) from 75 subjects of the Russian Federation. Specially designed questionnaires were used to obtain information on certain indicators from different sources. The study assessed the state of the infrastructure, collected information on staffing, identified conditions that have a negative impact on the quality and availability of psychological first aid.. According to the results of the study, quality criteria were identified and the directions and measures necessary for the provision of emergency psychological assistance were determined. It is concluded that the effectiveness of psychological assistance in crisis situations depends on the availability of qualified specialists and educational work with teachers and parents to develop skills for early detection of a crisis situation. Представлен анализ оказания экстренной психологической помощи в системе образования. Авторы отмечают, что научный интерес к оказанию экстренной психологической помощи в кризисных ситуациях обусловлен практическим запросом, так как кризисное происшествие несет угрозу для жизни и здоровья. Выборку составили 3 группы респондентов (12048 человек) из 75 субъектов Российской Федерации. В качестве инструментария использовались специально разработанные анкеты, позволяющие получить сведения по определенным индикаторам из разных источников. В ходе исследования проведена оценка состояния инфраструктуры, собраны сведения о кадровом обеспечении, выявлены условия, оказывающие негативное влияние на качество и доступность экстренной и кризисной психологической помощи. По результатам исследования были выделены критерии качества и определены направления и мероприятия, необходимые для оказания экстренной психологической помощи. Сделаны выводы, что эффективность работы по оказанию психологической помощи в кризисных ситуациях зависит от наличия квалифицированных специалистов и просветительской работы с педагогами и родителями по развитию навыков раннего выявления кризисной ситуации.